A Look Under the Carpet of a Successful Eradication Campaign Against Small Ruminant Lentiviruses - Fadri Vincenz; Maksym Samoilenko; Carlos Eduardo Abril; Patrik Zanolari; Giuseppe Bertoni; Beat Thomann (Pathogens)
Small ruminant lentiviruses (SRLVs) are widespread and have a long co-evolutionary history with their hosts, namely sheep and goats. These viruses induce insidious pathologies, causing significant financial losses and animal welfare issues for the affected flocks. In Switzerland, in the 1980s, an eradication campaign was launched targeting these viruses, exclusively in goats, eliminating the virulent SRLV-B strains from the goat population, in which SRLV-B-induced arthritis was prevalent. Nevertheless, although they do not seem to induce clinical diseases, SRLV-A strains continue to circulate in Swiss goats. For this study, we contacted farmers who had animals testing positive for these strains during the census from 2011 to 2012 and visited six of these flocks, conducting serological, virological, and clinical analyses of the animals. We confirmed the absence of SRLV-B; however, we have detected SRLV-A in these flocks. Positive and negative animals lived in close contact for ten years and, except for a small flock of 13 animals, 7 of which tested positive, the transmission of these viruses proved inefficient. None of the positive animals showed any pathology attributable to SRLV infection. These encouraging results allowed us to formulate recommendations for the continued surveillance of these viruses in the Swiss goat population.